2016
DOI: 10.1097/bot.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Patients With a “Surprise” Positive Culture After Nonunion Surgery

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 13 publications
3
33
0
Order By: Relevance
“…One retrospective multicentre study found 20% of nonunions treated in humans had positive intra-operative cultures at the time of definitive surgery with the absence of any signs of gross infection or preoperative symptoms. Of these, only 78% healed after the initial procedure, and 92% healed with subsequent procedures (33). Theoretically, avascular bone provides an ideal environment for bacterial growth, condyle of one case, limiting the surface area impacted by the graft.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…One retrospective multicentre study found 20% of nonunions treated in humans had positive intra-operative cultures at the time of definitive surgery with the absence of any signs of gross infection or preoperative symptoms. Of these, only 78% healed after the initial procedure, and 92% healed with subsequent procedures (33). Theoretically, avascular bone provides an ideal environment for bacterial growth, condyle of one case, limiting the surface area impacted by the graft.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Evaluating these clinical parameters is the first and foremost step in the diagnostic procedure for a nonunion patient with suspected infection. However, patients with typical clinical manifestations of infection are decreasing, while quiescent infections are rising in recent years [ 1 ]. Low virulence bacteria and “biofilm pathogens” surrounding the implant have been reported as the primary causes that induce indolent infection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…White blood cell (WBC) count, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) should be obtained, and their elevation, especially when combined, is a strong predictor of infection [7]. Additionally, intraoperative cultures should be obtained at the time of revision surgery even if there are no clinical signs of infection, as 20% of patients in a large multicenter series were shown to have positive cultures, with only 9% felt to be contaminants [12]. If infection is confirmed in the initial laboratory evaluation and surgical intervention is deemed necessary and safe, multiple treatment options exist.…”
Section: Nonunion Evaluationmentioning
confidence: 99%